Nepalese primiparous mothers' knowledge of newborn care. (28th April 2015) - Shrestha, Sharmila; Adachi, Kumiko; Petrini, Marcia A.; Shuda, Akihiro; Shrestha, Sarita
Abstract A cross‐sectional study was carried out to explore the knowledge level of newborn care and to investigate the relationship between newborn‐care knowledge and selected demographic variables among primiparous mothers. It was carried in outpatient department of a maternity and women's hospital in Kathmandu, Nepal with 276 primiparous mothers between 38 and 42 weeks of gestation. Data were collected during the antenatal period with using two instruments: the Newborn‐care Knowledge Questionnaire and State‐Trait Anxiety Inventory for Adults. Participants had a moderate level of knowledge on newborn care (56%), and among its four components, participants had lowest knowledge in breastfeeding (44%) and adequate knowledge (78%) of immunization. Maternal education and socioeconomic status had a significant, positive association with newborn‐care knowledge. Newborn‐care knowledge was strongly predicted by anxiety. This is the first study to examine the maternal levels of knowledge of newborn care in Nepal. This study identified specific knowledge gaps in newborn care among primiparous mothers. Moreover, the results suggest the need of maternal‐education programs in improving the health and well‐being of mothers and newborns.